2017
DOI: 10.1071/rd15143
|View full text |Cite
|
Sign up to set email alerts
|

Placenta-derived extracellular vesicles: their cargo and possible functions

Abstract: The literature on extracellular vesicles consists of rapidly expanding and often contradictory information. In this paper we attempt to review what is currently known regarding extracellular vesicles released specifically from human placental syncytiotrophoblast cells with a focus on the common but complex pregnancy-associated syndrome pre-eclampsia, where the level of syncytiotrophoblast extracellular vesicle release is significantly increased. We review common methods for syncytiotrophoblast extracellular ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 108 publications
4
53
0
2
Order By: Relevance
“…It is also possible the EV cargo is influenced by disease state, as recently suggested in the context of preeclampsia [8183], as well as the stage of pregnancy and the methodology used for analysis. [84]. Lastly, we note that EV subtypes might not be homogeneous [85].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible the EV cargo is influenced by disease state, as recently suggested in the context of preeclampsia [8183], as well as the stage of pregnancy and the methodology used for analysis. [84]. Lastly, we note that EV subtypes might not be homogeneous [85].…”
Section: Discussionmentioning
confidence: 99%
“…In a metaanalysis published in 2017, Familari et al [57] summarizing the results of six different studies, showed that only three proteins were consistently found in all studies, namely albumin, fibronectin-1 (FN1) and plasminogen activator inhibitor-1 (PAI-1). In a metaanalysis published in 2017, Familari et al [57] summarizing the results of six different studies, showed that only three proteins were consistently found in all studies, namely albumin, fibronectin-1 (FN1) and plasminogen activator inhibitor-1 (PAI-1).…”
Section: Trophoblast-derived Extracellular Vesicles: Characterizationmentioning
confidence: 99%
“…Several proteomic studies have investigated the composition of placenta-derived exosomes and MVs. In a metaanalysis published in 2017, Familari et al [57] summarizing the results of six different studies, showed that only three proteins were consistently found in all studies, namely albumin, fibronectin-1 (FN1) and plasminogen activator inhibitor-1 (PAI-1). The variability of the results obtained can be ascribed to differences in isolation techniques, placental age and to the interindividual genetic difference.…”
Section: Trophoblast-derived Extracellular Vesicles: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become increasingly clear that EVs perform a fundamental role in intercellular communication by fusing with target cells to deliver microRNAs, lipid, and protein cargo. Recent investigation has demonstrated a role for EV signaling in many cell types including EV regulation of myogenesis in myoblasts, sperm maturation, osteoclast precursor differentiation, and may regulate trophoblast fusion, suggesting the signaling role of EVs is a general cellular phenomenon (62, 69, 87, 88). …”
Section: Introductionmentioning
confidence: 99%